1988
DOI: 10.1002/pola.1988.080260217
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the benzoin isobutyl ether photoinitiated polymerization of styrene

Abstract: SynopsisThe kinetic3 of the photopolymerization of styrene in bulk and in dilute systems in the presence of benzoin isobutyl ether as photoinitiator have been examined. The values of the intensity exponent, calculated at different temperatures or at different styrene concentrations, and the monomer exponent, calculated at various intensities, showed significant departure from those predicted by the ideal kinetic scheme, particularly at high intensity, at low temperature, or at low styrene concentrations. Low m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…217 As another model monomer system, kinetic investigations of photopolymerization of St in the presence of benzoin have been carried out. 218,219 Kinetic data confirmed that the benzoyl radical is the dominant initiating species at low temperature, high intensity, and/or low monomer concentration, while the benzyl ether radical was almost terminated at the early stage of reaction. 219 Additionally, both benzoyl and benzyl ether radicals are capable of initiating polymerization at high temperature, low intensity, and/or high monomer concentration, which is an important supplementary finding to the benzoin-initiated polymerization investigated before.…”
Section: Photochemically Initiated Radical Polymerizationmentioning
confidence: 85%
See 1 more Smart Citation
“…217 As another model monomer system, kinetic investigations of photopolymerization of St in the presence of benzoin have been carried out. 218,219 Kinetic data confirmed that the benzoyl radical is the dominant initiating species at low temperature, high intensity, and/or low monomer concentration, while the benzyl ether radical was almost terminated at the early stage of reaction. 219 Additionally, both benzoyl and benzyl ether radicals are capable of initiating polymerization at high temperature, low intensity, and/or high monomer concentration, which is an important supplementary finding to the benzoin-initiated polymerization investigated before.…”
Section: Photochemically Initiated Radical Polymerizationmentioning
confidence: 85%
“…218,219 Kinetic data confirmed that the benzoyl radical is the dominant initiating species at low temperature, high intensity, and/or low monomer concentration, while the benzyl ether radical was almost terminated at the early stage of reaction. 219 Additionally, both benzoyl and benzyl ether radicals are capable of initiating polymerization at high temperature, low intensity, and/or high monomer concentration, which is an important supplementary finding to the benzoin-initiated polymerization investigated before. 206 As an extension, benzoin is preferentially selected for the pulse-laser initiated polymerization for evaluating various kinetic coefficients of FRP considering its excellent photochemical reactivity.…”
Section: Photochemically Initiated Radical Polymerizationmentioning
confidence: 85%
“…35 In contrast to PI 1 which are capable of generating initiator radicals independently, PI2 must undergo a bimolecular reaction, generally with H donors. The requirement of a bimolecular reaction for generation of initiator radicals by PI2 suggests that the efficiency of radical formation will decrease with increasing viscosity owing to lower diffusional rates.…”
Section: Organic Photoinitiators For Free Radical Polymerizationmentioning
confidence: 99%
“…In the design of this polymeric network, AA was expected to form the polymer main chains containing carboxylic acid groups, while DVB was introduced as a crosslinker to induce the interconnected polymeric networks. BIE and AIBN were used to initiate the free radical polymerization via photolysis [ 17 ] and thermolysis [ 18 ] under the UV irradiation where heat is generated, respectively. The formation of crosslinked polymeric networks as shown in Figure 1 was confirmed on the basis of the solubility test of AA-DVB membrane conducted in representative polar aprotic solvents (i.e., N-methyl-2-pyrrolidone, dimethylacetamide, dimethylsulfoxide, dimethylformamide) at 60 °C for one day.…”
Section: Resultsmentioning
confidence: 99%